Appraising A Sense of Community in Designing Senior Housing for Elderly Quality of Life - Ismail, Alice; Razak, Fairuz; Mohamad Faisal, Wan Nadiah (Journal of Architecture, Planning and Construction Management, 2021)
Malaysia’s life expectancy may increase by 2030, where the ageing population aged above 65 years and over is growing faster than all other age groups. It is expected that this ageing population will be more than 15% of the total population in the year 2030, and this percentage likely to rise higher over the next three decades. The increasing longevity indicates the climbing numbers of surviving older people, who demand better living and Quality of Life (QoL) later in life and retirement concerning housing, transportation, social participation and health services. However, the most critical issue is the elderly living housing, namely in developed countries where many still lack proper physical environment to accommodate and improve community development among the elderly. Consequently, the rights for appropriate, adequate, decent, and good quality housing for ageing people in either quantitative or qualitative approaches are not well acknowledged. This paper aims to highlight community importance as the elderly require a solid community to promote active ageing and life satisfaction, which is vital to be implemented in their living environments like the elderly housing design planning layout and form making. To achieve this, the first objective of this paper is to identify the sense of community index among the elderly and second to propose the best elderly housing design concept in terms of spatial planning and form making, which considers the sense of community indexes that supports independent living to enhance the Quality of Life (QoL) for the ageing population. This study used the mix method approach where data are collected from case studies through literature review and direct observations. The sense of community index comprising membership, influence, fulfilment, and shared emotional connections are analyzed to see its correlation and representation in the current case study of senior housing spatial design in Malaysia. The findings indicate that for senior housing to have a sense of community, architectural qualities like identifiable forms and spatial values with connected, shared spaces either at horizontal or vertical levels and vast shared public spaces are essential. This study helps establish the best living concept for elderly housing as a reference for developers, policymakers, and designers to produce proper senior housing to enhance Quality of Life (QoL).